The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/cmdc.201500490
|View full text |Cite
|
Sign up to set email alerts
|

Development of Highly Potent GAT1 Inhibitors: Synthesis of Nipecotic Acid Derivatives by Suzuki–Miyaura Cross‐Coupling Reactions

Abstract: A new series of potent and selective mGAT1 inhibitors has been identified, featuring a nipecotic acid residue and an N-butenyl linker with a 2-biphenyl residue at the ω-position. Docking, combined with MD calculations, revealed a binding mode for the new compounds similar to that of tiagabine, the only mGAT1 inhibitor currently approved as antiepileptic drug. For the synthesis, a Suzuki-Miyaura cross-coupling reaction was used as a key step by which variously substituted biaryl subunits were assembled. Biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…With mGAT1 binding affinities being in the range of 8.2–8.3 (p K i ), enantiomers ( R )‐ 17 d , ( R )‐ 17 f , ( R )‐ 17 g , and ( R )‐ 17 i , (Table , entries 4a, 6a, 7a, and 9a) are among the best binders known so far for this target. As compared with the 2′,4′‐dichloro‐substituted derivative of ( R )‐ 4 (p K i =8.33±0.06, pIC 50 =7.43±0.10), which is one of the most active mGAT1 inhibitors, the binding affinity of the most active mGAT1 inhibitors of this study was found to be in the same range, and their inhibitory potencies even somewhat higher. Relative to N ‐substituted derivatives of guvacine with an oxime spacer that are known to be among the most potent mGAT1 inhibitors to date, the best of the nipecotic acid derivatives with an alkyne spacer described in this study generally show inhibitory potencies (pIC 50 ) and binding affinities (p K i ) in a similar range.…”
Section: Resultsmentioning
confidence: 59%
See 4 more Smart Citations
“…With mGAT1 binding affinities being in the range of 8.2–8.3 (p K i ), enantiomers ( R )‐ 17 d , ( R )‐ 17 f , ( R )‐ 17 g , and ( R )‐ 17 i , (Table , entries 4a, 6a, 7a, and 9a) are among the best binders known so far for this target. As compared with the 2′,4′‐dichloro‐substituted derivative of ( R )‐ 4 (p K i =8.33±0.06, pIC 50 =7.43±0.10), which is one of the most active mGAT1 inhibitors, the binding affinity of the most active mGAT1 inhibitors of this study was found to be in the same range, and their inhibitory potencies even somewhat higher. Relative to N ‐substituted derivatives of guvacine with an oxime spacer that are known to be among the most potent mGAT1 inhibitors to date, the best of the nipecotic acid derivatives with an alkyne spacer described in this study generally show inhibitory potencies (pIC 50 ) and binding affinities (p K i ) in a similar range.…”
Section: Resultsmentioning
confidence: 59%
“…We recently introduced compounds 5 and 6 (Figure ) and related derivatives, the lipophilic part of which is characterized by a biphenylvinyl or a benzylphenylvinyl unit. For the parent compounds 5 and 6 , high binding affinities for GAT1 were observed ( 5 : p K i =7.15±0.07; 6 : p K i =6.16±0.07) . For the biphenyl derivative 5 , docking studies indicated that halogen substitution of the terminal phenyl group might provide compounds with enhanced binding affinities for hGAT1; this was indeed verified, as halogen‐substituted derivatives of 5 were found to exhibit binding affinities of p K i ≥8.…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations